Estetika Tinjauan Terapan Ukiran Pada Produk Mebel Di Daerah Jepara - Mesah Nur Sejati (Penerbit Itenas, 2024)
Background: Aesthetics is a term used to express everything that concerns beauty that can be seen with the naked eye. One of the aesthetic reviews of applied carvings on furniture products in the Jepara area is carved reliefs. Works of fine art that penetrate the observer's feelings so that they become happy, comfortable and satisfied occur because of the aesthetic value impressed in the art. Carved reliefs are an art object, therefore, to be able to say that an object has an aesthetic form, it can be seen from its design. The aim of the research on the application of carving here is to observe the aesthetics of carving applied to Jepara furniture, where there are very diverse techniques applied. Research Method: Qualitative. This research consists of two stages, namely the first stage conducting a survey about the phenomenon of applied carving on furniture in Jepara; The second stage was conducting an exploratory study to collect data about the application of carvings to furniture in Jepara. Sampling technique: Purposive sampling. Consists of 10 participants. Result: The carving application produces a very attractive aesthetic resulting in shape, size, material and color. The conclusion of this research is that in the Jepara area there are many carvings with various shapes and appearances that are very meaningful. This appearance makes it characteristic and differentiates it from other areas. The study of aesthetic elements is very meaningful. The shape has characteristics that show the originality of the element for future researchers. The form has a unique application that can lead to innovation. The theme suggestions that we have taken here provide very strong originality, especially in the applied study of the aesthetics of carvings to furniture. Becomes evidence in the development of aesthetic science, applied review of carving for furniture products, especially in product design courses.